Encapsulation of Moluccan albizia's (Paraserianthes falcataria) seeds to support tree plantation program in urban areas - HARMASTINI SUKIMAN; SYLVIA LEKATOMPESSY; TIWIT WIDOWATI; LISEU NURJANAH; NURIYANAH NURIYANAH (Smujo International, 2015)
Abstract. Sukiman H, Lekatompessy S, Widowati T, Nurjanah L, Nuriyanah. 2015. Encapsulation of Mollucan albizia’s (Paraserianthes falcataria) seeds to support tree plantation program in urban areas. Nusantara Bioscience 7: 128-132.Green open space in urban areas and their outskirt is an essential requirement for healthy and clean cities. The success of tree plantation program requires the availability of high-quality seeds. Several relevant researches have produced technologies which can support tree plantation programs, among others, are seed encapsulation methods and the use of microbes for biological fertilizers. Encapsulation of seeds is aimed at protecting the seeds from extreme conditions that may occur during germination and, at the same time, providing microbes for the seedling growth. Results showed that nitrogen-fixing bacteria could be included in various materials of carriers for Moluccan albizia’s (Paraserianthes falcataria) seeds. The microbes which grow in agar media as a carrier become the best encapsulation method compare to microbes grow in other carriers.